Komizm w "Dziejach" Herodota z Halikarnasu – wybrane przykłady - Wieżel, Iwona (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
In the present article I discuss the comic elements engaged by Herodotus in the verbal stratum and content of the Histories. Therefore, I analyze puns as a stylistic devise used by Historian to put an emphasis on some parts of the narrative, esp. on the ethnographic and historical one, after that I discuss selected episodes paying special attention to their ironic dimension. I also try to show how Herodotus uses his literary technique in its comic range not only to make the public of his oral presentations laughing but also to teach them how to live in the wise manner but not without the humour itself. Because Docere apart from Delectare was one of the main purposes of the ancient historical writing.
Humor in the Histories of Herodotus – selected examples
Keywords: Herodotus of Halicarnassus; Histories; Humour; Irony; Narrative